Changes in the renal and extrarenal handling of phosphate induced by disodium etidronate (EHDP) in man. - Walton, R; Russell, R; Smith, R (1975)
1. The diphosphonate, disodium etidronate (disodium ethane-1-hydroxy-1, 1-diphosphonate; (EHDP), is known to increase plasma inorganic phosphate in man. The present study examines the mechanism of this effect. 2. When EHDP was given by mouth at a dose of 80 mumol (20 mg) kg-minus 1day-minus 1, plasma phosphate was significantly increased 24 h after the first dose but did not reach its maximum value for 2-3 weeks. When the drug was stopped, plasma phosphate returned to pretreatment values within 3 weeks. 3. Urinary excretion rate of phosphate was not greatly changed during treatment with EHDP despite the large increase in plasma phosphate, suggesting an alteration in renal handling. This was examined directly by infusing phosphate and inulin in six patients off and on EDPH. 4. EHDP had no effect on glomerular filtration rate (GFR) but produced a large increase in the maximum rate of renal tubular reabsorption of phosphate (TmP). The ratio Tm,P/GFR increased from a mean value of 1.15 mmol/1 to 2.10 mmol/1 on EHDP. This increase accounted for the hyperphosphataemia. 5. The same amount of phosphate infused at the same rate produced a greater rise in plasma phosphate when patients were on EHDP than when they were not, indicating a reduced net rate of entry of phosphate into tissues other than kidney. 6. Fasting total plasma calcium concentration and urine calcium excretion rate were not significantly altered by EHDP but the ability of infused phosphate to decrease plasma calcium was diminished. 7. It is suggested that EHDP alters phosphate transport in kidney and other tissues by a mechanism which is probably independent of the known hormonal influences on phosphate metabolism.